PITUITARY HISTOMORPHOLOGY OF THE GRASS CARF CTENOPHARYNGODON IDELLA (VALENCIENNES) - DAS, RADHA. C.; KHAN, HASIB A.; REDDY, P. V. G. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
The adenohy?ophysis of C. idella is divisible into rostral pars distalis (RPD), proximal pars distalis (PPD) and pars intermedia (PI). Aldehyde fuchsin (AF) positive neurohypophysial fibres penetrate into the pars intermedia region. On the basis of tinctorial and histochemical properties seven cell types of chromophils and 8th cell type of chromophobes have been identi. fied. The RPD contains cell type 1, 2 and 3. The PP D contains type 4 acidophils and type 3 and 5 cyanophils. The PI is composed of two cell types PbH positive and PAS positive cells Chromophobes take no stain and constitute the 8th cell type located in all the component parts of the adenohypophysis. Cell types described in the adenohypophysis of other teleosts are also discussed.